Cultural Hybridity in the Dutch East Indies: Paul Johan Seelig’s Piano Concerto as a Reflection of Colonial Identity - Indah, Kasih Karunia (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to examine the first movement of the Piano Concerto in F-Sharp Minor by Paul Johan Seelig, focusing on the relationship between Western classical music and the music of the Dutch East Indies during the 1910s–1930s through Édouard Glissant’s concept of rhizomatic identity. The research employs a qualitative method with data collection techniques, including archival studies and literature reviews. Analysis was conducted using Paul Ricoeur’s hermeneutic approach, encompassing the study of the work’s background, structure, and appropriation in a broader context. The findings reveal that the first movement of the Piano Concerto in F-Sharp Minor reflects a hybrid cultural identity that integrates Western classical music idioms with local musical elements from the Dutch East Indies, such as the adaptation of the Lagoe Soenda melody into patterns resembling gamelan. This transformation reflects a respect for local culture rooted in Nusantara traditions while simultaneously reinterpreting it within the framework of Western classical music. The work not only represents artistic dynamics but also serves as a socio-cultural document illustrating power relations and intercultural dialogue in the colonial context. Seelig highlighted local themes to bridge cultural gaps, showcasing the potential of local music as a medium equal to Western musical traditions. The study’s findings reveal that cultural identity in Seelig’s work is not static but emerges as the dynamic interaction between two distinct traditions. This approach contrasts with other colonial composers, such as Claude Debussy, who tended to adopt aesthetic impressions without retaining local themes. This research contributes to expanding the understanding of socio-cultural relations through colonial music and underscores the significance of music as a medium that can represent social dynamics, identity, and power during the colonial era. Beyond its theoretical contributions, the study offers a new perspective on hybrid music and cultural appropriation. This approach is relevant for fostering awareness of the importance of intercultural dialogue in the arts while demonstrating how music can serve as a tool for bridging cultural differences and transcending colonial hierarchies.